Link stability metric based on mobility prediction model in mobile ad hoc networks - ZHANG Hui1; DONG Yu-ning1 (Tongxin xuebao)
A mobility prediction model based stable link selection algorithm was proposed in which stable neighbor met-ric and local movement metric were defined.Mobility prediction model was applied to predict stability probabilities be-tween each local node and its neighbors by using those two metrics and LZ78 algorithm so as to find the most stable neighbor of each local node and most stable route in a route discovery.The simulation results show that the algorithm outperforms the histogram algorithm and the lowest ID algorithm in selecting stable links.